SPLIT LATERAL FOREHEAD FLAP FOR RECONSTRUCTION OF UPPER AND LOWER EYELIDS - Pramana, I G. A. N. Widya; Rizaliyana, Sitti (Universitas Airlangga, 2019)
Highlights: Split Lateral Forehead Flap Technique was successful. Eyelid Reconstruction was Challenging. Abstract: Introduction: Eyelids reconstruction after tumor resection has be one of the most challenging procedures in reconstructive plastic surgery. Small defects may be closed by primary suture or covered by small local flaps or skin graft. But in large eyelids defects, we need to find a bigger source of color and texture matching tissue that will ensure functional and aesthetical outcomes. Many techniques have been described, but in this case, the author suggest a split lateral forehead flap designed to cover upper and lower eyelids. Case Illustration: A Male 51 years-old-patient, presented himself in our clinic with a basal cell carcinoma involving the right upper and lower eyelids. The tumor had a history of 7 years, without any pain or vision disorders involved. Tumor was widely excised, leaving a full thickness on upper and lower eyelids. The inner lining palpebral was replaced by composite auricular graft following by lateral cantophexy. A lateral forehead flap raised with a right temporal pedicle, and the distal part of flap was split in half, and inset into the upper and lower eyelids defect. The donor region was closed with an STSG from Femur Dextra. After 14 days the flap was divided, the functional result was excellent. Discussion: At first, surgeons were worried of raising forehead flaps beyond the midline, fearing that by splitting the distal flap would cause its compropmise. However, rich anastomostic plexus exists between the major forehead angiosomes lined by the smaller calibre